Nilai Nilai Pendidikan Islam Dalam Mengenakan Cadar Mahasiswi Fakultas Tarbiyah Dan Keguruan UIN Antasari Banjarmasin - Surawardi, Surawardi (STAI AL FALAH Banjarbaru, 2021)
This research was motivated by a phenomenon of the use of veils in the campus environment of UIN Antasari Banjarmasin, especially the Faculty of Tarbiyah and Teacher Training. Users believe in many values of Islamic education obtained, namely First; Aspects of civilization and progress, habituation of well-dressed. Clothing like this will be able to protect her religious beliefs, reputation, and the highest value of women is to maintain shame and self-respect. Second; The value of moral education in a more perfect direction, both zhahir and batin. Third; Keeping his holiness, taking better care of himself, is very authoritative in all his motions and silence, the more self-esteem and height of his position in the eyes of men, so that they are easier to know and not disturbed. Fourth; Responsibility to themselves, education values moral values to obey worship, maintain morality and improve themselves a lot from the mistakes they once did in the past. Fifth; The intention of obeying the teachings of Islam and the intention of worship because of Allah. The main thing is the fulfilment of Islamic religious norms well, although the Qur'an does not explain the obligation to cover the face there is no harm if it is done by women in keeping themselves from something unwanted. The results of the study found there were several supporting factors and obstacles for students of the Faculty of Tarbiyah and UIN Teacher Training Antasari Banjarmasin in wearing the veil. Keywords: values, education, wearers and veils.